Analysis of Quality Management of Islamic Education at the Pabelan Islamic Boarding School, Mungkid District, Magelang Regency - Wardana, Billy Eka; Usman, Nurodin; Guilin, Xie; Jiao, Deng (Journal International Inspire Education Technology, 2023)
Abstract— This study aims to describe the management of Islamic education institutions to improve the quality of Islamic boarding schools. This research phase consisted of a number of activities, namely (1) examining the units of analysis, (2) mapping the management models of Islamic educational institutions, and (3) analyzing the management model of Islamic education to improve the quality of education in the research object. The Islamic boarding school chosen as the research location is the Pabelan Islamic Boarding School, Magelang. Pabelan Islamic Boarding School is a boarding school that has proven its existence and has graduated many alumni who are widely active in Indonesia. To facilitate this research, researchers used the theory of quality management of Islamic educational institutions which is based on four quality indicators, namely (1) the quality of graduates, (2) the quality of the learning process, (3) the quality of school services and (4) the quality of the school environment. The research method uses a qualitative descriptive method. The research subjects were leaders, senior teachers and students. The research subjects were the analysis of the quality management of the Kulliyatul Mu'allim Al-Islamiyah Pabelan Islamic Boarding School and confirmation of the correctness of the material through source triangulation and method triangulation. The results of the analysis are expected to be able to formulate quality management for Islamic educational institutions in Indonesia. This study will analyze strategies to improve the quality of education, the factors that support and inhibit the process of improving the quality of education, and the efforts made by the Pabelan Islamic Boarding School in improving the quality of education